Protocol of the adaptive study of IL-2 dose frequency on regulatory T cells in type 1 diabetes (DILfrequency): a mechanistic, non-randomised, repeat dose, open-label, response-adaptive study. Issue 12 (8th December 2015) - Truman, Lucy A; Pekalski, Marcin L; Kareclas, Paula; Evangelou, Marina; Walker, Neil M; Howlett, James; Mander, Adrian P; Kennet, Jane; Wicker, Linda S; Bond, Simon; Todd, John A; Waldron-Lynch, Frank
Abstract : Introduction: Type 1 diabetes (T1D) is caused by autoimmune destruction of the insulin-producing β cells in the pancreatic islets, leading to insulinopenia and hyperglycaemia. Genetic analyses indicate that alterations of the interleukin-2 (IL-2) pathway mediating immune activation and tolerance predispose to T1D, specifically the polymorphic expression of the IL-2 receptor-α chain (CD25) on T lymphocytes. Replacement of physiological doses of IL-2 could restore self-tolerance and prevent further autoimmunity by enhancing the function of CD4 + T regulatory cells (Tregs) to limit the activation of auto reactive T effector cells (Teffs). In this experimental medicine study, we use an adaptive trial design to determine the optimal dosing regimen for IL-2 to improve Treg function while limiting activation of Teffs in participants with T1D. Methods and analysis: The Ad aptive study of IL- 2 dose frequency on Tregs in type 1 diabetes(DILfrequency) is a mechanistic, non-randomised, repeat dose open-label, response-adaptive study of 36 participants with T1D. The objective is to establish the optimal dose and frequency of ultra-low dose IL-2: to increase Treg frequency within the physiological range, to increase CD25 expression on Tregs, without increasing CD4 + Teffs. DILfrequency has an initial learning phase where 12 participants are allocated to six different doses and frequencies followed by an interim statistical analysis. After analysis of the learning phase, the Dose and Frequency Committee will select the optimal targets for Treg frequency, Treg CD25 expression and Teff frequency. Three groups of eight participants will be treated consecutively in the confirming phase. Each dose and frequency selected will be based on statistical analysis of all data collected from the previous groups. Ethics: Ethical approval for DILfrequency was granted on 12 August 2014. Results: The results of this study will be reported, through peer-reviewed journals, conference presentations and an internal organisational report. Trial registration numbers: NCT02265809, ISRCTN40319192, CRN17571.